Measurement of sludge-water interface based on adjustable peak point of ultrasonic echo energy - Miao Li; Yang Miao; Fengying Zhou; Yongqiang Yang; Huan Huang (PLoS ONE, 2026)
To address the escalating water resources consumption, the need for intelligent automation in urban sewage treatment has become imperative. However, existing ultrasonic sludge interface instruments have been found to exhibit poor environmental noise suppression and low identification accuracy of mud-water interface, thereby necessitating a new approach. This paper analyzes the problems and proposes a mud-water interface monitoring method based on extraction of ultrasonic energy peak point. The method involves an array ultrasonic system structure comprising multiple ultrasonic transmitting and receiving elements, median value average filtering to suppress peak noise interference, and interval maximum method to separate the target peak point from residual noise. The proposed method was tested using a high-precision ultrasonic probe in Beijing Ma-Fang Sewage Treatment Plant and corrected using a fault diagnosis method with 3σ threshold. Results demonstrated a high measurement accuracy with a mean deviation of less than 2% and a precision variance below ±0.02 m. Compared to conventional ultrasonic and optical methods, this approach exhibited superior robustness in turbid environments, fully meeting the technical requirements of sludge thickness monitoring.